Understanding Local Culture Through Museum Tourism In Anthropological Perspective At Museum Bank Indonesia - Awaloedin, Dipa Teruna; Pradini, Gagih; Agustiani, Fitri; Ramadaniyah, Dinda Nisaa; Yazid, Muhammad Sholah; Nur, Ahmad Regi (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2024)
Museums are institutions that play a central role in preserving, presenting, and disseminating the cultural heritage of a community. In the context of tourism, museums are not only a place to store historical artifacts, but also an attractive destination for tourists who want to understand more about local culture. Museum tourism, with its focus on anthropological aspects, opens the door to an immersive experience of understanding local culture. The Bank Indonesia Museum, as an institution that not only displays the historical heritage of economics and banking but also interprets the role of local culture in that context, offers a unique arena for analyzing the interaction between visitors and local culture. Through an anthropological perspective, this study aims to explore how museum tourism at the Bank Indonesia Museum can be a means of a rich understanding of local culture, as well as how these experiences shape visitors' perceptions and understandings of the cultural richness of an area. This research method uses a descriptive qualitative approach and SWOT analysis.